Delegated Legislation in the Light of Taxation Laws: A Case Study of Pakistan - Dhariwal, Ahtesham; Gondal, Naveed Mushtaq; Zahid, Muhammad Umar; Arshad, Madeeha (Law and Policy Review, 2025)
When legislative authority is granted to bodies other than the legislature, the legislation created by these bodies is referred to as delegated legislation (Singh, 2023). Legislation is the primary job of the people’s representatives, called legislature. The need for delegated legislation in taxation laws arises due to evolving social norms and advancements in technology, such as the introduction of online filing of tax returns. These rapid changes have overburdened the legislatures and also exposed the lack of technical knowledge, prompting the transfer of legislative powers to the sub-ordinate departments of the government. This study employs an exploratory research methodology to investigate the concept and role of delegated legislation in the area of taxation laws in Pakistan. The area is explored based on the relevant laws, court decisions, and published articles. The role of delegated legislation in the context of taxation laws, misuse of authority, and discretionary powers exercised by the authorities is probed. The findings demonstrate that the provision for delegated legislation in the 1973 Constitution of the Islamic Republic of Pakistan was included with a specific purpose and is subject to certain restrictions. Under the taxation laws of Pakistan, the powers can be delegated to subordinates to achieve certain goals. The lawmakers establish the structure, and authorize the executives to make their own rules for smooth functioning, provided they remain within the boundaries defined by the legislature. Through delegation of powers, the function can only be performed by the officer of a certain rank. It is pertinent to mention that the authority to delegate powers can never be further delegated to any person.